Triptolide Induces Liver Injury by Regulating Macrophage Recruitment and Polarization via the Nrf2 Signaling Pathway. (20th June 2022) - Liu, Li; Zhang, Xi; Xing, Xin; Mohammed, Ismail; Xu, Xiao-ting; Jiang, Zhen-zhou; Wang, Tao; Huang, Xin; Wang, Xin-zhi; Zhang, Lu-yong; Sun, Li-xin
Abstract : Triptolide (TP) has limited usage in clinical practice due to its side effects and toxicity, especially liver injury. Hepatic macrophages, key player of liver innate immunity, were found to be recruited and activated by TP in our previous study. The nuclear factor-erythroid-2-related factor 2 (Nrf2) pathway exerts a protective role in TP-induced liver damage, but its effect on the functions of hepatic macrophage has not been elucidated. Here, we determined whether TP can regulate the recruitment and polarization of hepatic macrophages by inhibiting Nrf2 signaling cascade. Our results demonstrated that TP inhibited the Nrf2 signaling pathway in hepatic macrophages. The changes in hepatic macrophages were responsible for the increased susceptibility toward inflammatory stimuli, and hence, TP pretreatment could induce severe liver damage upon the stimulation of a nontoxic dose of lipopolysaccharides. In addition, the Nrf2 agonist protected macrophages from TP-induced toxicity and Nrf2 deficiency significantly aggravated liver injury by enhancing the recruitment and M1 polarization of hepatic macrophages. This study suggests that Nrf2 pathway-mediated hepatic macrophage polarization plays an essential role in TP-induced liver damage, which can serve as a potential therapeutic target for preventing hepatotoxicity induced by TP.